Control over π-π stacking of heteroheptacene-based nonfullerene acceptors for 16% efficiency polymer solar cells. Issue 12 (25th August 2020) - Ma, Yunlong; Cai, Dongdong; Wan, Shuo; Yin, Pan; Wang, Pengsong; Lin, Wenyuan; Zheng, Qingdong
Abstract: Nonfullerene acceptors are being investigated for use in polymer solar cells (PSCs), with their advantages of extending the absorption range, reducing the energy loss and therefore enhancing the power conversion efficiency (PCE). However, to further boost the PCE, mobilities of these nonfullerene acceptors should be improved. For nonfullerene acceptors, the π–π stacking distance between cofacially stacked molecules significantly affects their mobility. Here, we demonstrate a strategy to increase the mobility of heteroheptacene-based nonfullerene acceptors by reducing their π–π stacking distances via control over the bulkiness of lateral side chains. Incorporation of 2-butyloctyl substituents into the nonfullerene acceptor (M36) leads to an increased mobility with a reduced π–π stacking distance of 3.45 Å. Consequently, M36 affords an enhanced PCE of 16%, which is the highest among all acceptor-donor-acceptor-type nonfullerene acceptors to date. This strategy of control over the bulkiness of side chains on nonfullerene acceptors should aid the development of more efficient PSCs.